Suicidal Death due to Organophosphorus Compound Poisoning ? an Experience of 67 Cases (Journal of Enam Medical College, 2016)
Background: Bangladesh is an agro-based country. Suicide by agrochemical compounds are increasing day by day in this country. Organophosphorus compounds (OPC) are commonly used for suicide. Mostly these are used for suicidal purpose in rural areas in our country due to low cost, toxicity and availability.Objective: To find out the relationship of age and sex variation along with the causes that influenced different income group people to ingest OPC for committing suicide.Materials and Methods: This study was conducted in the Department of Forensic Medicine, Dhaka Medical College during January to December 2010. Data were collected at the time of autopsy and from postmortem examination report of viscera. Viscera were preserved and sent to the Chief Chemical Examiners Office, Dhaka for toxicological analysis.Results: In this study, middle aged subjects (2030 years) were found to commit suicide using OPC in comparison to other age groups. Among the cases male were 57% and female 43%. Poverty was found as the most common cause (20%) of OPC poisoning.Conclusion: Poverty is the leading cause of death of OPC poisoning followed by failure in love and adultery. Business failure, unhappiness in conjugal life, demand for dowry and violence against women are other causes to commit suicide by OPC.J Enam Med Col 2016; 6(2): 97-100